Developing an Integrative SMART Learning Model to Support Holistic Development in Early Childhood Education - Nita Priyanti; Rita Mariyana; Rika Sadiyah; Debie Susanti; Restu Yuningsih (Ta'dib, 2025)
Learning practices in early childhood education have not yet optimally integrated science, mathematics, art, religious values, and technology into a unified instructional model. This study aims to develop and examine the effectiveness of the SMART learning model (Science, Math, Art, Religion, and Technology) in early childhood education. Using a research and development (R&D) approach, the study integrated quantitative and qualitative data and involved early childhood learners as research participants. The model was developed through the ADDIE framework and validated by early childhood education experts, classroom teachers, and religious education specialists. The findings indicate that the SMART learning model is more effective than conventional lecture-based learning in enhancing children’s competencies across science, mathematics, art, religion, and technology. Overall, the study demonstrates that the SMART learning model provides an integrative, child-centered approach that supports holistic learning outcomes and aligns with early childhood developmental characteristics.